(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il dilemma etico ai tempi della pandemia da Covid-19 -2. Le Raccomandazioni di etica clinica della SIIARTI del 6 marzo 2020 - 3. I criteri selettivi di accesso ai reparti di terapia intensiva in Svizzera, Quebec (Canada) e Alabama (USA) - 4. Triage in emergenza pandemica. Possibile contrasto di alcuni criteri selettivi con i valori religiosi ed etici del personale sanitario -5. Emergenza sanitaria e “clausola di coscienza” in Italia. Science and conscience at the time of the Covid-19 health emergency ABASTRACT: The Covid-19 pandemic crisis and the saturation of the intensive care wards have made it necessary to prepare patient selection criteria in case of lack of available places. The spread of various "selective criteria", in different regulatory realities, starting in Italy from the Ethical Recommendations of the SIIARTI (Italian Society of Anaesthesia, Analgesia, Resuscitation and Intensive Care) of March 6, 2020, as well as for reasons of distributive justice and appropriate allocation of limited health resources, was also necessary to relieve medical staff from part of the responsibility in the choices to be made, sometimes particularly onerous. The rationale behind the "medicine of catastrophes" documents, however, may conflict with the ethical values of medical personnel, undoubtedly capable of influencing their professional choices. The present contribution aims to verify the configurability of a space within which to give prominence, even in emergency conditions, to the ethical-religious beliefs of health personnel, in accordance with the rules of medical and nursing ethics that allow the individual operator to invoke the "conscience clause" to justify the refusal of services considered contrary to their conscience or their technical-scientific beliefs, even in cases not recognized by laws that expressly provide for "conscientious objection".